The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acsanm.2c00354
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl-Enriched Core/Shell Carbon Nanotubes for Catalytic Hydrolysis of Regenerated Cellulose to Glucose

Abstract: A hydroxyl-enriched core/shell structured carbon nanotube (CNT/C-OH) is prepared by the method of hydrothermal carbonization (HTC) as a catalytic accelerator to induce highly efficient hydrolysis of regenerated cellulose to glucose. By use of sonication with high sound intensity, the carbon source (namely glucose) is homogeneously dispersed with CNT to form a colloid. Accordingly, a high-quality CNT/C-OH with a hydroxyl-enriched coating layer is produced in the following HTC. The oxygen mass content of the she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…That is because the hydroxyl-rich carbon layer-coated CNTs provided rather strong adsorption to break the aggregate structure of cellulose. Accordingly, the acid catalyst can more easily enter the inside of cellulose to enhance the hydrolytic responsiveness of the glycosidic bond. ,, These results showed that the hydroxyl-rich carbon layer on the surface of CNTs played an important role in the hydrolysis of cellulose to sugar.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…That is because the hydroxyl-rich carbon layer-coated CNTs provided rather strong adsorption to break the aggregate structure of cellulose. Accordingly, the acid catalyst can more easily enter the inside of cellulose to enhance the hydrolytic responsiveness of the glycosidic bond. ,, These results showed that the hydroxyl-rich carbon layer on the surface of CNTs played an important role in the hydrolysis of cellulose to sugar.…”
Section: Resultsmentioning
confidence: 95%
“…The utilization rate of the carbon source and the quality of the coating on the CNTs are not high. In our previous work, 34 with the aim to strengthen the dispersion between the carbon source and CNTs and then enhance the utilization of the carbon source, a method driven by sonication with high sound intensity was tried to treat the mixture of CNTs and glucose. Accordingly, it can be found that the amount of associated carbon spheres obviously decreases during the coating of CNTs in HTC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the O1s spectrum of Figure 3 c, three peaks at the binding energies of 531.0, 532.3 and 533.1 eV were also obtained after fitting. The first one is attributed to the lattice oxygen of ZnO, and the last two correspond to C−O−H and C−O−C bonds originating from cellulose, PPL and PVA [ 16 , 48 , 49 , 50 , 51 ]. The Zn2p spectrum showed a typical doublet peak at 1021.9 and 1045.0 eV, which were Zn2p 3/2 and Zn2p 1/2 of divalent Zn element, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous research, 10,11,[43][44][45][46][47] we embarked on the research endeavor to develop cellulase-mimetic catalysts by using a rational design approach to introduce strong adsorption with cellulose into solid catalysts. Utilizing the strong adsorption to break down the aggregation structure of cellulose enhances the hydrolytic responsibility of glycosidic bonds particularly instead of the function of traditional strong acids.…”
Section: Introductionmentioning
confidence: 99%